Inklusifitas Sekolah Sasaran Program Kampus Mengajar pada SMP Negeri Satu Atap di Kabupaten Wonosobo - Robingun Suyud El Syam; Salis Irvan Fuadi (STIKes Ibnu Sina Ajibarang, 2023)
Purpose: The article aims to explore the inclusiveness of the target schools of the Teaching Campus Program at One Roof Public Middle Schools in Wonosobo Regency, by emphasizing findings that characterize the portrait of education in rural schools. Methodology: Research is a combination of quantitative and qualitative. Data was collected through literature study, news and articles in both online and offline media, as well as interviews with the Secretary of the Wonosobo Regency Education, Youth and Sports Service, School Principals, teaching staff and students of the Teaching Campus program. Next, the data is analyzed and strengthened with various theoretical supports in the discussion. Findings: The inclusiveness of education at the target school of the Teaching Campus in terms of attitudes and educational patterns is different from schools in urban areas, where they understand more about education from the surrounding environment. This opens up the opportunity for a dichotomy curriculum between one region and another. This research contributes to theory, practice and future research directions in the field of educational curriculum. We propose that scientific organizations can push the boundaries of scientific progress, moving beyond power structures by integrating the principle of diversity as a consideration in national curricula. Originality: research integrates educational inclusiveness in rural areas, where previous research has not been specific in approach.